1980
DOI: 10.2337/diacare.3.5.594
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Health Belief Model and Compliance of Persons with Diabetes Mellitus

Abstract: Thirty insulin-treated diabetic individuals were interviewed in their homes 6-12 mo after having attended diabetic education classes at a community hospital. Self-report as well as direct observation were used to measure these patients' level of compliance with their insulin administration, urine testing, diet, hypoglycemia management, and foot care prescriptions. All patients were complying with at least 59% of the points measured. Over one-half of the group indicated compliance with at least 70% of the 61 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0
2

Year Published

1986
1986
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(112 citation statements)
references
References 0 publications
4
106
0
2
Order By: Relevance
“…In addition, the questionnaire contained fixed choice questions pertaining to the specific knowledge of the basic fundamentals of DM and certain aspects of management, statements consisting of a self-report of activities regarding the ability to follow dietary prescription and continuing adherence to daily caloric limit; the ability to use small amounts of food to avoid the hypoglycemic effect of insulin; reliability in insulin administration (or the use of hypoglycemic agents), enquiries into the importance of exercise, proper foot and skin care, urine and blood glucose home monitoring. Lastly, the questionnaire consisted of 13 statements that evaluated areas considered important for diabetes management such as the participant's satisfaction with the physician, her adjustment to DM [13][14][15] and the absence of major role disruption (inability to keep house, disrupted social relationship, etc. ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the questionnaire contained fixed choice questions pertaining to the specific knowledge of the basic fundamentals of DM and certain aspects of management, statements consisting of a self-report of activities regarding the ability to follow dietary prescription and continuing adherence to daily caloric limit; the ability to use small amounts of food to avoid the hypoglycemic effect of insulin; reliability in insulin administration (or the use of hypoglycemic agents), enquiries into the importance of exercise, proper foot and skin care, urine and blood glucose home monitoring. Lastly, the questionnaire consisted of 13 statements that evaluated areas considered important for diabetes management such as the participant's satisfaction with the physician, her adjustment to DM [13][14][15] and the absence of major role disruption (inability to keep house, disrupted social relationship, etc. ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies sometimes calculated a total score for self-management [13,14], but researchers now agree that different aspects of self-management should be assessed separately because of its multidimensional nature [15][16][17]. A variety of questionnaires have been developed, most of which focus on the frequency with which people perform their selfmanagement tasks in a variety of areas.…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that orthodox treatment is not as popular with the population under study as it is in the western world [26,27]. Perceived benefits of, and barriers to, treatment regimen play a vital role in achieving therapeutic success [28]. However, patients in our study seem unsatisfied with medication prescribed to them.…”
Section: Formentioning
confidence: 60%